Fenomena Komunikasi Muslimat Bercadar melalui Media Sosial di Pekanbaru (The Communication Phenomenon of Woman Muslim Wearing Veil through Social Media in Pekanbaru) - Adriani Rahmida Hayati; Yasir Yasir; Noor Efni Salam (Jurnal Dakwah Risalah, 2020)
This study aims to describe the phenomenon of veiled muslim woman communication in Pekanbaru in using social media. This research reveals the communication experience, self-concept, and motives of veiled muslim women through the use of social media, with qualitative methods and phenomenological approaches. The results showed that the experience of veiled muslim women communication using social media from various aspects, with the best experience of meeting new fellow Muslims, to the unpleasant experience was considered a terrorist. Their self-concept in the use of social media is to create a positive self-concept with a friendly nature because the Islamic religion teaches creating good relationships among muslims as the Prophet of Allah exhorts. Other motives, veiled muslim women use social media as a means of promotion for businesses, obtain religious studies, and communication for understanding religious beliefs.